ANALISIS PENGARUH CLEANING TUBING KONDENSOR TERHADAP PERFORMA SISTEM REFRIGERASI MESIN WATER COOLED CHILLER KAPASITAS 650TR - Agung Pranoto; Hablinur Al Kindi; Gatot Eka Pramono (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The condenser needs to be cleaned so that the performance of the heat exchanger can optimally. This research was conducted on a water cooled chiller machine with a capacity of 650TR and the type of refrigerant used is R134a to determine the performance of the machine after cleaning process. The electric power used by the compressor’s motor before there was a fouling, fouling and after cleaning the condenser tubing were 174,80 kW, 191,22 kW and 174,42 kW respectively. The mass flow rate of cooling water before there is a fouling, fouling and after cleaning the condenser tubing is 98,01 kg/s, 106,74 kg/s and 126,15 kg/s respectively. The actual cooling load before there is a fouling, fouling and after cleaning the condenser tubing is 1352,46 kW, 1343,27 kW and 1363,92 kW respectively. Heat rejected before there is a fouling, fouling and after cleaning the condenser tubing is 1527,26 kW, 1534,49 kW and 1538,34 kW respectively. Coefficient of performance heating before there is a fouling, fouling and after cleaning the condenser tubing is 8,75, 8,04 and 8,82 respectively. Based on the results of the research, the performance of the water cooled chiller machine has increased after cleaning the condenser tubing.